Functional Outcome Trajectories Following Inpatient Rehabilitation for TBI in the United States: A NIDILRR TBIMS and CDC Interagency Collaboration. Issue 2 (March 2020) - Dams-O'Connor, Kristen; Ketchum, Jessica M.; Cuthbert, Jeffrey P.; Corrigan, John D.; Hammond, Flora M.; Haarbauer-Krupa, Juliet; Kowalski, Robert G.; Miller, A. Cate
Abstract : Objective: To describe trajectories of functioning up to 5 years after traumatic brain injury (TBI) that required inpatient rehabilitation in the United States using individual growth curve models conditioned on factors associated with variability in functioning and independence over time. Design: Secondary analysis of population-weighted data from a multicenter longitudinal cohort study. Setting: Acute inpatient rehabilitation facilities. Participants: A total of 4624 individuals 16 years and older with a primary diagnosis of TBI. Main Outcome Measures: Ratings of global disability and supervision needs as reported by participants or proxy during follow-up telephone interviews at 1, 2, and 5 years postinjury. Results: Many TBI survivors experience functional improvement through 1 and 2 years postinjury, followed by a decline in functioning and decreased independence by 5 years. However, there was considerable heterogeneity in outcomes across individuals. Factors such as older age, non-White race, lower preinjury productivity, public payer source, longer length of inpatient rehabilitation stay, and lower discharge functional status were found to negatively impact trajectories of change over time. Conclusions: These findings can inform the content, timing, and target recipients of interventions designed to maximize functional independence after TBI. Abstract : Supplemental Digital Content is Available in the Text.